Carbon nanotube / graphite hybrid material, preparation method thereof and lithium ion battery
By modifying the expanded graphite with a nonionic surfactant and generating carbon nanotubes by chemical vapor deposition, the problems of poor dispersion and high contact resistance of the carbon nanotube/graphite composite materials are solved, and efficient preparation of the material and excellent conductivity are achieved.
Patent Information
- Application Number
- CN202411984856.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-01
AI Technical Summary
The existing carbon nanotube/graphite composite materials have problems such as poor dispersion, high contact resistance, complex preparation process and high energy consumption in applications, which affect their performance in lithium-ion batteries and other fields.
The expanded graphite is modified by a nonionic surfactant, and carbon nanotubes are formed between the graphite layers by chemical vapor deposition to form a metal-supported graphite catalyst to promote the uniform dispersion and chemical connection between the carbon nanotubes and graphite.
It significantly reduces the contact resistance between carbon nanotubes and graphite, improves the conductivity and dispersion of the material, simplifies the preparation process, reduces energy consumption, and improves the electrochemical performance of lithium-ion batteries.
Smart Images

Figure CN119742354A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of carbon materials, and specifically relates to a carbon nanotube / graphite hybrid material and a preparation method thereof, and a lithium-ion battery. Background Art
[0002] Carbon nanotubes and graphene have been well promoted and applied in many advanced fields due to their excellent electrical, thermal, mechanical and chemical properties. However, the nanoscale structures of carbon nanotubes and graphene often lead to anisotropy and aggregation problems, which affect the performance of such carbon materials in practical applications. For example, when used as functional composite material additives, water purification fillers and energy storage / conversion electrode materials, it may affect the product performance of the corresponding products. Due to the interaction and van der Waals forces between individuals, carbon nanotubes and graphene are prone to agglomeration, resulting in a reduction in active surface area, which is also not conducive to the transmission of electrons in each axial direction.
[0003] The integration of one-dimensional carbon nanotubes and two-dimensional graphene can be used as an effective strategy to construct multi-scale structures with complementary properties, which can improve the specific surface area and conductivity of carbon materials. A common method is to physically mix carbon nanotubes and graphene to obtain a hybrid by a solution method. However, the combination of these two types of carbon materials in a common physical overlap is easily affected by the contact resistance between carbon nanotubes and graphene, which limits the transfer of electrons and affects their performance.
[0004] In order to reduce the overall dispersibility of carbon nanotube / graphite composites, the commonly used methods are ultrasonic dispersion of the raw materials, ball milling or graphite surface functionalization, but these methods generally have problems such as complex operating procedures, harsh reaction conditions, and low efficiency, which invisibly increases the preparation cost of the materials.
[0005] CN114639806A discloses a method for preparing a graphite carbon nanotube composite electrode material, comprising: placing graphite in a metal salt aqueous solution, ball milling and drying, calcining the obtained solid in a protective gas to obtain a catalyst / graphite; then heating polyolefin to obtain a pyrolysis reaction gas, introducing the pyrolysis reaction gas into the protective gas to contact the catalyst / graphite to perform a heating catalytic reaction, and obtaining a graphite carbon nanotube composite electrode material. The preparation procedure of this method is complicated, and it is necessary to ball mill the graphite and pyrolyze the polyolefin. The energy consumption in the preparation process is high and the efficiency is low. In addition, the method uses nitrates, hydrochlorides, and sulfates as the main metal sources for catalyst loading. The gases generated by these metal salts during drying and roasting are easy to corrode equipment and exhaust pipes, and also pollute the environment.
[0006] CN102610827A discloses a composite material formed by expanded graphite and carbon nanotubes, which is used as a conductive additive for lithium batteries. The preparation method mainly includes: inserting one or more of iron, nickel or cobalt into the expanded graphite interlayer; growing carbon nanotubes in the expanded graphite interlayer using a gas phase catalytic process. The method requires heat treatment of 12 to 48 hours at a high temperature of 400 to 700 ° C in an air-tight state for inserting metal into the expanded graphite interlayer. The reaction conditions are relatively harsh, the preparation efficiency is low, the dispersion effect of the active catalyst on the graphite surface is poor, the loading rate is low, and the generation rate of carbon nanotubes is affected. Summary of the invention
[0007] In order to overcome the above-mentioned defects of the prior art, the purpose of the present application is to provide a carbon nanotube / graphite hybrid material and a preparation method thereof and a lithium ion battery. The method of the present application can efficiently prepare a carbon nanotube / graphite hybrid material. In the prepared carbon nanotube / graphite hybrid material, there is a good electron transmission path between the carbon nanotube and the graphite, and the application in a lithium ion battery can effectively improve the electrochemical performance of the battery.
[0008] To achieve the above objectives, the first aspect of the present application provides a method for preparing a carbon nanotube / graphite hybrid material, comprising:
[0009] (1) Preparation of metal-supported graphite catalyst
[0010] 1-1) mixing a surfactant, expanded graphite and water and performing a first stirring to obtain a graphite dispersion, and then removing water from the graphite dispersion to obtain modified graphite; wherein the surfactant comprises a nonionic surfactant;
[0011] 1-2) mixing the modified graphite, a soluble metal salt, water and an optional ammonium salt and performing a second stirring to obtain a metal salt-graphite dispersion; wherein the soluble metal salt comprises a main catalyst salt and an optional auxiliary catalyst salt, the main catalyst salt comprises iron citrate, and the auxiliary catalyst salt comprises a molybdenum salt;
[0012] 1-3) removing water from the metal salt-graphite dispersion, and calcining the obtained solid product at 300-500° C. to obtain a metal-supported graphite catalyst;
[0013] (2) Preparation of carbon nanotube / graphite hybrid materials
[0014] Under the protection of inert gas, the metal-supported graphite catalyst is brought into contact with a reducing gas and a carbon source gas, and the carbon source gas is used to perform chemical vapor deposition to form carbon nanotubes, thereby obtaining a carbon nanotube / graphite hybrid material.
[0015] In the preparation method of the present application, a nonionic surfactant is used to modify the expanded graphite, which can effectively improve the binding ability between the graphite interlayer surface and the metal ions, and promote the uniform dispersion of the metal ions in the graphite interlayer; using iron citrate as the iron source can make the iron active particles evenly dispersed on the graphite surface and alleviate the particle agglomeration during roasting, and the use of low-temperature roasting can not only reduce energy consumption, but also avoid the aggregation of metal active particles caused by high-temperature roasting and the oxidative damage to the graphite structure caused by high temperature; in addition, the prepared metal-loaded graphite catalyst can efficiently catalyze the carbon source gas to generate carbon nanotubes between the graphite layers by chemical vapor deposition and reducing gas reduction. The prepared carbon nanotube / graphite hybrid material can significantly reduce the contact resistance between the carbon nanotube and the graphite compared to the carbon nanotube / graphite composite material formed by physical mixing, and the feeding method in the present application also promotes the uniform distribution of graphite in the carbon nanotube, which is beneficial to subsequent applications.
[0016] In some embodiments of the present application, the ammonium salt is at least one of ammonium carbonate and ammonium bicarbonate.
[0017] In some embodiments of the present application, the iron citrate is ammonium ferric citrate and / or ferric citrate.
[0018] Preferably, the iron citrate is ammonium ferric citrate. The metal salt-graphite dispersion containing ammonium ferric citrate has better wettability to the modified graphite, can form more hydrogen bonds with the oxygen-containing groups of the modified graphite, and improves the adsorption capacity of the graphite to the iron salt and the anchored iron nanoparticles. Ammonium ferric citrate will form NH4OH during low-temperature calcination, and NH4OH will release excess NH3 when heated, further inhibiting the thermal agglomeration of iron particles.
[0019] In some embodiments of the present application, the iron citrate is ferric citrate, and in step 1-2), the mass ratio of ferric citrate to ammonium salt is (2-8):1.
[0020] In some embodiments of the present application, the nonionic surfactant is a polyoxyethylene ether surfactant.
[0021] Furthermore, the polyoxyethylene ether surfactant is selected from alkylphenol polyoxyethylene ether and / or lauryl alcohol polyoxyethylene ether.
[0022] Furthermore, the polyoxyethylene ether surfactant is selected from one or more of octylphenol polyoxyethylene ether, nonylphenol polyoxyethylene ether, dodecylphenol polyoxyethylene ether, dinonylphenol polyoxyethylene ether and lauryl alcohol polyoxyethylene ether.
[0023] In some embodiments of the present application, the mass ratio of the surfactant to the expanded graphite is (2-10):100.
[0024] In some embodiments of the present application, the mass ratio of the expanded graphite to water is (15-30):100.
[0025] In some embodiments of the present application, the first stirring temperature is 20 to 40° C., and the stirring time is 0.5 to 2 h.
[0026] In some embodiments of the present application, the method of removing water from the graphite dispersion includes:
[0027] The graphite dispersion is stirred at 50-80° C. for 2-8 hours.
[0028] In some embodiments of the present application, the mass ratio of the main catalyst salt to the auxiliary catalyst salt is (15-30): 1. The auxiliary catalyst helps to regulate the electronic structure of the main catalyst, and a small amount of auxiliary catalyst salt can increase the catalyst activity and promote carbon conversion.
[0029] In some embodiments of the present application, the mass ratio of the soluble metal salt to the modified graphite is (1.2-3): 1. Too low a loading of the metal salt may result in low catalytic conversion efficiency, while too high a loading may result in easy agglomeration of nano-metal particles and reduced utilization.
[0030] In some embodiments of the present application, the main catalyst salt also includes a cobalt salt.
[0031] Furthermore, the cobalt salt is cobalt nitrate and / or cobalt nitrate hydrate.
[0032] Furthermore, the mass ratio of the iron citrate to the cobalt salt is (3-10):1.
[0033] In some embodiments of the present application, in step 1-2), the mass ratio of the soluble metal salt to water is (30-50):100.
[0034] In some embodiments of the present application, the molybdenum salt is ammonium molybdate and / or ammonium molybdate hydrate.
[0035] In some embodiments of the present application, the second stirring temperature is 50 to 80° C., and the stirring time is 1 to 5 hours.
[0036] In some embodiments of the present application, water in the metal salt-graphite dispersion is removed in the following manner: the metal salt-graphite dispersion is stirred at 100-180° C. for 2-6 hours.
[0037] In some embodiments of the present application, the calcination is performed in an oxygen-containing atmosphere, and the calcination time is 1 to 5 hours.
[0038] In some embodiments of the present application, in the chemical vapor deposition, relative to 3 g of the metal-supported graphite catalyst, the flow rate of the reducing gas is 80 to 120 sccm, and the flow rate of the carbon source gas is 800 to 1500 sccm.
[0039] In some embodiments of the present application, the carbon source gas is selected from at least one of methane, acetylene, ethylene and propylene.
[0040] In some embodiments of the present application, the reducing gas is hydrogen.
[0041] In some embodiments of the present application, the temperature of the chemical vapor deposition is 600-800° C., and the time is 30-60 min.
[0042] The second aspect of the present application provides a carbon nanotube / graphite hybrid material prepared by the preparation method of the first aspect of the present application.
[0043] The third aspect of the present application provides a lithium-ion battery comprising a conductive additive, wherein the conductive additive comprises the carbon nanotube / graphite hybrid material described in the second aspect of the present application.
[0044] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0045] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0046] Figure 1 is a scanning electron microscope image (SEM) of the carbon nanotube / graphite hybrid material of Example 1;
[0047] Figure 2 Impedance spectra of the carbon nanotube / graphite hybrid material of Example 1 and the carbon nanotube / graphite composite material of Comparative Example 4;
[0048] Figure 3 This is a comparison chart of the discharge gram capacity changes at different rates of lithium-ion batteries prepared using the carbon nanotube / graphite hybrid material of Example 1 and the carbon nanotube / graphite composite material of Comparative Example 4 as conductive additives. DETAILED DESCRIPTION
[0049] The following describes the implementation of the present application in detail. The implementation described below is exemplary and is only used to explain the present application, and cannot be understood as limiting the present application.
[0050] The "range" disclosed in the present application is defined in the form of a lower limit and / or an upper limit, and a given range is defined by selecting a lower limit and / or an upper limit. The range defined in this way can be inclusive or exclusive of end values, and can be combined arbitrarily, that is, any lower limit can be combined with any upper limit to form an unclearly recorded range, and any lower limit can be combined with other lower limits to form an unclearly recorded range, and any upper limit can be combined with any other upper limit to form an unclearly recorded range. In addition, each separately disclosed point or single value itself can be combined with any other point or single value as a lower limit or upper limit or with other lower limits or upper limits to form an unclearly recorded range.
[0051] If not otherwise specified, all embodiments and optional embodiments of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.
[0052] In the present application, the terms “first” and “second” are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the quantity of the indicated technical features.
[0053] In a first aspect, the present application provides a method for preparing a carbon nanotube / graphite hybrid material, comprising:
[0054] (1) Preparation of metal-supported graphite catalyst
[0055] 1-1) mixing a surfactant, expanded graphite and water and performing a first stirring to obtain a graphite dispersion, and then removing water from the graphite dispersion to obtain modified graphite;
[0056] 1-2) mixing the modified graphite, a soluble metal salt, water and an optional ammonium salt and performing a second stirring to obtain a metal salt-graphite dispersion;
[0057] 1-3) removing water from the metal salt-graphite dispersion, and calcining the obtained solid product (precursor) at a low temperature to obtain a metal-supported graphite catalyst;
[0058] (2) Preparation of carbon nanotube / graphite hybrid materials
[0059] Under the protection of inert gas, the metal-supported graphite catalyst is brought into contact with a reducing gas and a carbon source gas, and the carbon source gas is used to perform chemical vapor deposition to form carbon nanotubes, thereby obtaining a carbon nanotube / graphite hybrid material.
[0060] According to the present application, step (1) is intended to form a graphite-based catalyst loaded with an active component (metal), specifically including step 1-1) for forming the modified graphite and steps 1-2) and 1-3) for loading to form a catalyst.
[0061] In step 1-1), the surfactant includes a nonionic surfactant. Modifying expanded graphite (EG) with a nonionic surfactant can effectively improve the surface activity of EG. Compared with ionic surfactants, the hydrophilic and hydrophobic groups in nonionic surfactants are stably present in aqueous solution through steric hindrance effects, are not affected by electrolytes and pH changes in the solution, and are insensitive to temperature changes. They can maintain stable surface activity within a wide temperature range, so that the modified graphite always maintains high binding force and dispersion ability for metal ions during the preparation of the catalyst, so that the prepared catalyst always maintains high catalytic activity during the process of chemical vapor deposition to form carbon nanotubes.
[0062] In some embodiments, the nonionic surfactant is a polyvinyl ether surfactant.
[0063] Preferably, the polyoxyethylene ether surfactant is selected from alkylphenol polyoxyethylene ether and / or fatty alcohol polyoxyethylene ether. Such surfactants not only have high stability, but also the hydrophilic groups (hydroxyl or phenolic groups, etc.) in their molecules can form hydrogen bonds or solvation with water, making it easier to penetrate into the graphite interior or make the graphite surface fully wetted by water, while allowing metal salts to fully diffuse into the graphite interlayer. In addition, metal ions can also bind to hydroxyl / phenolic groups through coordination bonds, and are fixed on the graphite surface through surfactant molecule bridging, promoting the uniform dispersion of metal ions.
[0064] Preferably, the polyoxyethylene ether surfactant is selected from one or more of octylphenol polyoxyethylene ether, nonylphenol polyoxyethylene ether, dodecylphenol polyoxyethylene ether, dinonylphenol polyoxyethylene ether and lauryl alcohol polyoxyethylene ether.
[0065] In some embodiments, the mass ratio of the surfactant to the expanded graphite is (2-10):100, such as 2:100, 3:100, 4:100, 4.5:100, 5:100, 6:100, 8:100, 10:100, etc. This can not only promote the modification of graphite, but also reduce the possibility of particles agglomerating due to excessive surfactant dosage and affecting the diffusion of metal ions.
[0066] In some embodiments, in step 1-1), the mass ratio of the expanded graphite to water may be (15-30):100, for example, 15:100, 18:100, 20:100, 22:100, 25:100, 30:100, etc.
[0067] In some embodiments, the first stirring temperature may be 20-40°C, for example, 20°C, 25°C, 30°C, 35°C, 40°C, etc.; the first stirring time may be 0.5-2h, for example, 0.5h, 0.8h, 1h, 1.5h, 2h, etc.
[0068] As an example, the first stirring is performed at room temperature.
[0069] Preferably, the graphite dispersion is stirred at 50-80° C. for 2-8 hours to remove water from the graphite dispersion.
[0070] In step 1-2), as the source of active components in the supported graphite catalyst, the soluble metal salt includes a main catalyst salt and an optional auxiliary catalyst salt, preferably includes a main catalyst salt and an auxiliary catalyst salt.
[0071] In some embodiments, the mass ratio of the main catalyst salt to the auxiliary catalyst salt can be (15-30):1, for example, 15:1, 16:1, 17:1, 17.5:1, 18:1, 18.4:1, 19:1, 20:1, 22:1, 23:1, 26:1, 28:1, 29:1, 30:1, etc.
[0072] According to the present application, the main catalyst salt is used to provide active components including Fe, and includes iron citrate. Compared with the use of inorganic iron salts, the use of iron citrate as an iron source can not only promote the uniform dispersion of active components on the surface of modified graphite and alleviate agglomeration during roasting, but also effectively alleviate the irreversible loss of equipment caused by exhaust gas generated during roasting.
[0073] In some embodiments, the ammonium salt is at least one of ammonium carbonate and ammonium bicarbonate.
[0074] In some embodiments, the iron citrate is ammonium ferric citrate and / or ferric citrate.
[0075] Preferably, the iron citrate is ammonium ferric citrate. The inventors found in the study that the ammonium ferric citrate solution has good wettability on the modified graphite and can form more hydrogen bonds with the oxygen groups of the modified graphite, which greatly improves the adsorption capacity of the modified graphite for ammonium ferric citrate and the anchored iron nanoparticles after calcination; not only that, the NH3 released by ammonium ferric citrate during the calcination process can further inhibit the thermal agglomeration of iron particles and reduce the particle size of the catalyst; in addition, NH3 can also be doped in the graphite structure to form CN functional sites, which can enhance the binding ability of graphite with metal sites.
[0076] In step 1-2), the ammonium salt may or may not be added. When the iron citrate is ferric citrate, the ammonium salt is preferably added. As a reaction aid, the ammonium salt can release NH3 when decomposed by heat, which can inhibit the thermal agglomeration of iron particles. Based on the mass amount of water in step 1-2), the mass amount of the ammonium salt can be 0-12%.
[0077] In some embodiments, the main catalyst salt includes ferric citrate, and the mass ratio of ferric citrate to ammonium salt is (2-8):1, for example, 2:1, 3:1, 3.2:1, 3.5:1, 3.6:1, 4:1, 5:1, 6:1, 7:1, 8:1, etc.
[0078] Optionally, the main catalyst salt may further include other metal salts, for example, one or more selected from the following soluble metal salts: cobalt salts, nickel salts.
[0079] In some embodiments, the main catalyst salt also includes a cobalt salt. The cobalt salt can maintain activity for a long time under high temperature and reducing atmosphere, is not easy to be deactivated or poisoned, and can increase the active sites of the catalytic reaction. The cobalt salt and the iron salt are used together to promote the carbon source to form carbon nanotubes with relatively uniform thickness, further improving the yield and quality of the carbon nanotubes.
[0080] Preferably, the cobalt salt is cobalt nitrate (Co(NO3)2) and / or a hydrate of cobalt nitrate (eg, Co(NO3)2·6H2O).
[0081] Preferably, the mass ratio of the iron citrate to the cobalt salt is (3-10):1, for example, 3:1, 5:1, 5.5:1, 6:1, 7:1, 8:1, 9:1, 10:1, etc.
[0082] According to the present application, the co-catalyst salt is used to provide co-catalyst active components including Mo, and the co-catalyst salt includes a molybdenum salt.
[0083] Optionally, the co-catalyst salt further includes one or more of the following soluble salts: vanadium salts (such as ammonium vanadate), tungsten salts, and zirconium salts.
[0084] The molybdenum salt can be selected from various soluble molybdenum sources. According to some embodiments, the molybdenum salt is ammonium molybdate ((NH)MoO) and / or ammonium molybdate hydrate (e.g., (NH4)4MoO6·4H2O).
[0085] In step 1-2), the second stirring can cause the soluble metal salt to be evenly distributed on the interlayer surface of the modified graphite. In order to improve the diffusion ability of metal ions in aqueous solution, the second stirring is preferably carried out at a temperature higher than room temperature. According to one embodiment, the temperature of the second stirring is 50 to 80°C, such as 50°C, 60°C, 65°C, 70°C, 75°C, 80°C, etc.; the time of the second stirring is 1 to 5h, such as 1h, 1.5h, 2h, 3h, 4h, 5h, etc.
[0086] In some embodiments, the mass ratio of the soluble metal salt to the modified graphite is (1.2-3):1, for example, 1.2:1, 1.3:1, 1.4:1, 1.5:1, 1.6:1, 1.7:1, 1.9:1, 2.3:1, 2.5:1, etc.
[0087] In some embodiments, the mass ratio of the soluble metal salt to water is (30-50):100, for example, 30:100, 31:100, 32:100, 35:100, 36:100, 38:100, 40:100, 45:100, 47:100, 48:100, 50:100, etc.
[0088] Preferably, water in the metal salt-graphite dispersion is removed by heating and stirring the metal salt-graphite dispersion at 100-180° C. for 2-6 hours. This condition can not only increase the drying rate, but also inhibit the local aggregation of metal salts caused by uneven internal heat transfer during the drying process.
[0089] In step 1-3), the solid product is calcined at 300-500° C. to generate uniformly distributed metal oxide particles. Too low a temperature will prevent the citrate from being completely decomposed and affect the crystallization of the metal oxide, while too high a temperature will cause oxidative damage to the modified graphite.
[0090] As some examples, the calcination temperature may be 300°C, 350°C, 380°C, 400°C, 420°C, 430°C, 450°C, 470°C, 485°C, 500°C, etc.
[0091] In some embodiments, the calcination may be performed in an oxygen-containing atmosphere (such as oxygen, air), and the calcination time may be 1 to 5 hours, for example, 1 hour, 2 hours, 2.5 hours, 3 hours, 4 hours, 4.5 hours, 5 hours, etc.
[0092] As some examples, the calcination is performed in a muffle furnace.
[0093] In step (2), under the protection of inert gas, the metal compound in the metal-supported graphite catalyst can be reduced to metal nanoparticles (e.g., iron particles, molybdenum particles, iron-molybdenum alloy particles) by reducing gas to improve catalytic activity. After reduction treatment, the metal element particles can be evenly distributed between the modified graphite layers, and the carbon source gas is catalyzed to form carbon nanotubes on the inner surface (between the layers) of the graphite through high-temperature pyrolysis, thereby achieving the exfoliation of the graphite to form graphene microsheets.
[0094] The present application does not particularly limit the inert gas, as long as it does not participate in the reaction. Specific examples of the inert gas include, but are not limited to, nitrogen and argon.
[0095] According to the present application, the reducing gas is, for example, hydrogen. The amount of the reducing gas can be selected according to the amount of the catalyst. According to some embodiments, in the chemical vapor deposition, relative to 3g of the metal-supported graphite catalyst, the amount of the reducing gas is 80 to 120 sccm, for example, 100 sccm.
[0096] According to the present application, the carbon source gas can be selected from various gaseous carbon sources that can be used to form carbon nanotubes. Preferably, the carbon source gas is an organic carbon source, which can produce hydrogen when cracked at high temperature, so that the catalyst maintains a high catalytic activity during the formation of carbon nanotubes. According to some embodiments, the carbon source gas is selected from at least one of methane, acetylene, ethylene and propylene.
[0097] In some embodiments, in the chemical vapor deposition, the flow rate of the carbon source gas is 800 to 1500 sccm, for example, 1000 sccm, relative to 3 g of the supported graphite catalyst. Too low a carbon source gas dosage may result in a low carbon nanotube content in the hybrid material, while too high a carbon source gas dosage may result in a carbon deposition rate higher than a carbon precipitation rate during the catalytic process, causing rapid deactivation of active sites and affecting catalyst utilization.
[0098] According to the present application, carbon nanotubes can be grown in situ on graphite sheets by chemical vapor deposition. According to some embodiments, the temperature of chemical vapor deposition is 600-800°C, such as 600°C, 650°C, 680°C, 700°C, 730°C, 750°C, 780°C, etc.
[0099] In some embodiments, the chemical vapor deposition time may be 30 to 60 minutes.
[0100] According to some specific implementations, step (2) includes the following process flow:
[0101] The metal-supported graphite catalyst is loaded in a tubular furnace, an inert gas is introduced, and under the protection of the inert gas, the temperature of the tubular furnace is raised to 600-800° C. at a rate of 5-10° C. / min; a carbon source gas and a reducing gas are then introduced to react for 30-60 minutes, the introduction of the carbon source gas and the reducing gas is stopped, and the furnace body is cooled to room temperature under the protection of the inert gas to obtain a carbon nanotube / graphite hybrid material.
[0102] The preparation method of the present application completes the modification of the graphite layer surface through a simple and mild reaction, which can effectively promote the anchoring and uniform dispersion of metal ions, and improve the loading rate of active metal catalysts between graphite layers. The method has the advantages of simple process and low cost, which is conducive to the industrial production of carbon nanotube / graphite composite materials. Furthermore, in the carbon nanotube / graphite hybrid material prepared by the method of the present application, the carbon nanotube can be chemically connected to the graphite through a covalent bond. Compared with physically blending the carbon nanotube and the graphite, the method of the present application can effectively reduce the contact resistance between the carbon nanotube and the graphite, and improve the uniformity of the dispersion between the two.
[0103] To this end, in a second aspect, the present application provides a carbon nanotube / graphite hybrid material prepared by the preparation method described in the first aspect of the present application.
[0104] According to the present application, generally as the carbon nanotube content increases, the resistivity of the carbon nanotube / graphite hybrid material decreases and the conductivity increases. Preferably, in the carbon nanotube / graphite hybrid material, the mass content of carbon nanotubes is not less than 80%.
[0105] In a third aspect, the present application provides a lithium-ion battery, wherein the lithium-ion battery comprises a conductive additive, wherein the conductive additive comprises the carbon nanotube / graphite hybrid material described in the second aspect of the present application.
[0106] Generally, the lithium-ion battery may include a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. During the battery charging and discharging process, active ions are embedded and extracted back and forth between the positive electrode sheet and the negative electrode sheet, the electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet, and the separator is arranged between the positive electrode sheet and the negative electrode sheet to prevent the positive and negative electrodes from short-circuiting and allow ions to pass through. Unless otherwise specified, the specific composition of the lithium-ion battery is well known in the art and will not be repeated here.
[0107] According to the present application, the carbon nanotube / graphite hybrid material can be used as a conductive additive in a positive electrode sheet, and can also be used as a conductive additive in a negative electrode sheet.
[0108] According to some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer located on the surface of the positive electrode current collector, and the positive electrode film layer includes a positive electrode material, a conductive additive and a binder, wherein the conductive additive includes the carbon nanotube / graphite hybrid material described in the second aspect of the present application. In this way, the rate performance and cycle stability of the lithium-ion battery can be effectively improved.
[0109] The following describes embodiments of the present application. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application.
[0110] In the following examples and comparative examples,
[0111] Example 1
[0112] Dissolve 1.5g of OP-10 in 100mL of deionized water, add 25g of expanded graphite, and stir at room temperature (25°C) for 1h to obtain a graphite dispersion. Then heat the graphite dispersion to 60°C, stir for 4h, and volatilize the water to obtain modified graphite. Dissolve 36g of ammonium ferric citrate and 1.96g of ammonium molybdate in 100mL of deionized water, add 25g of modified graphite, heat and stir at 60°C for 2h, then heat to 120°C, stir for 4h and dry, and calcine the dried powder at 350°C for 2h to obtain a Fe-Mo supported graphite catalyst.
[0113] 3 g of Fe-Mo supported graphite catalyst was loaded into a tubular furnace, and nitrogen was introduced at a flow rate of 2000 sccm for 30 min. The reactor was heated to 700 ° C at a rate of 10 ° C / min, and propylene (1000 sccm) and hydrogen (100 sccm) were continuously introduced at this temperature for 30 min. The introduction of propylene and hydrogen was stopped, and the nitrogen flow rate was adjusted to 5000 sccm for 15 min. Then, the nitrogen flow rate was reduced to 1000 sccm, and the reactor was naturally cooled to room temperature to obtain a carbon nanotube / graphite hybrid material, which was recorded as KNG-CG.
[0114] Figure 1 The SEM image of KNG-CG microstructure shows that the image mainly contains a group of carbon nanotubes with disordered linear structure and a small amount of graphite with lamellar material. It can be seen that Example 1 peels off the modified graphite into graphene microsheets with thin layer morphology while generating carbon nanotubes, and successfully prepares carbon nanotube / graphite hybrid material.
[0115] Example 2
[0116] A carbon nanotube / graphite hybrid material was prepared according to the method of Example 1, except that 36 g of ammonium ferric citrate was replaced by 35 g of ferric citrate and 9.7 g of ammonium carbonate.
[0117] Comparative Examples 1-2
[0118] A carbon nanotube / graphite composite material was prepared by referring to the method of Example 1, except that OP-10 was replaced by polyvinyl pyrrolidone (PVP) and cetyltrimethylammonium bromide (CTAB).
[0119] Comparative Example 3
[0120] A carbon nanotube / graphite composite material was prepared according to the method of Example 1, except that ammonium ferric citrate was replaced with 55.9 g of ferric nitrate nonahydrate.
[0121] Comparative Example 4
[0122] Carbon nanotubes (type is multi-walled carbon nanotubes) and expanded graphite are physically mixed at a mass ratio of 15:1 as a comparative sample. The specific operation steps are as follows:
[0123] A total of 16 g of carbon nanotubes and expanded graphite were added to a beaker containing 100 mL of deionized water and ultrasonically dispersed at room temperature for 30 minutes. The resulting dispersion was vacuum filtered to achieve solid-liquid separation, and the filter cake was transferred to a 60°C oven and dried for 6 h to obtain a carbon nanotube / graphite composite material, recorded as KNG-C / G.
[0124] Example 3
[0125] A carbon nanotube / graphite hybrid material was prepared according to the method of Example 1, except that 36 g of ammonium ferric citrate was replaced with 27 g of ammonium ferric citrate and 4.1 g of cobalt nitrate hexahydrate, thereby obtaining a carbon nanotube / graphite hybrid material.
[0126] Example 4
[0127] Dissolve 2g of OP-10 in 100mL of deionized water, add 25g of expanded graphite, and stir at room temperature for 1h to obtain a graphite dispersion. Heat the graphite dispersion to 60°C and stir for 4h and evaporate the water to obtain modified graphite. Dissolve 45g of ammonium ferric citrate and 1.96g of ammonium molybdate in 100mL of deionized water, add 25g of modified graphite, heat and stir at 60°C for 3h, then heat to 150°C and stir for 3h to dry, and calcine the dried powder at 430°C for 2h to obtain a Fe-Mo supported graphite catalyst.
[0128] 3 g of Fe-Mo supported graphite catalyst was loaded into a tubular furnace, and nitrogen was introduced at a flow rate of 2000 sccm for 30 minutes. The reactor was heated to 700° C. at a rate of 10° C. / min, and propylene (1000 sccm) and hydrogen (100 sccm) were continuously introduced at this temperature for reaction for 30 minutes. The introduction of propylene and hydrogen was stopped, and the nitrogen flow rate was adjusted to 5000 sccm for 15 minutes. Subsequently, the nitrogen flow rate was reduced to 1000 sccm, and the reactor was naturally cooled to room temperature to obtain a carbon nanotube / graphite hybrid material.
[0129] Example 5
[0130] Dissolve 1g of OP-10 in 100mL of deionized water, add 20g of expanded graphite, stir at room temperature for 1h to obtain a graphite dispersion. Heat the graphite dispersion to 60°C, stir for 4h and evaporate the water to obtain modified graphite. Dissolve 36g of ammonium ferric citrate, 4.1g of cobalt nitrate hexahydrate and 1.96g of ammonium molybdate in 100mL of deionized water, add 20g of modified graphite, heat and stir at 60°C for 3h, then heat to 150°C, stir for 3h and dry, and calcine the dried powder at 400°C for 1.5h to obtain a Fe-Co-Mo supported graphite catalyst.
[0131] 3 g of Fe-Co-Mo supported graphite catalyst was loaded into a tubular furnace, and nitrogen was introduced at a flow rate of 2500 sccm for 30 minutes. The reactor was heated to 700°C at a rate of 10°C / min, and propylene (1200 sccm) and hydrogen (100 sccm) were continuously introduced at this temperature for reaction for 30 minutes. The introduction of propylene and hydrogen was stopped, and the nitrogen flow rate was adjusted to 5000 sccm for 15 minutes. Subsequently, the nitrogen flow rate was reduced to 1000 sccm, and the reactor was naturally cooled to room temperature to obtain a carbon nanotube / graphite hybrid material.
[0132] Example 6
[0133] A carbon nanotube / graphite hybrid material was prepared according to the method of Example 1, except that OP-10 was replaced by lauryl alcohol polyoxyethylene ether.
[0134] Example 7
[0135] A carbon nanotube / graphite hybrid material was prepared according to the method of Example 6, except that 36 g of ammonium ferric citrate was replaced by 30 g of ammonium ferric citrate and 8.7 g of cobalt nitrate hexahydrate.
[0136] The growth rates and resistance properties of the carbon nanotubes (CNTs) of Examples 1 to 7 and Comparative Examples 1 to 4 are shown in Table 1.
[0137] CNT growth rate = (product mass - catalyst amount) / catalyst amount; the units of product mass and catalyst amount are both g.
[0138] Resistivity: The powder resistivity was tested using a GM-I multifunctional powder material resistivity automatic tester, sample weight: 1.3 g, pressure: 784 N.
[0139] Table 1
[0140] Serial number Product mass / g CNT growth rate Resistivity (μΩ·m) Example 1 48 15 789.4 Example 2 39 12 861.8 Comparative Example 1 12 3 1198.3 Comparative Example 2 24 7 941.2 Comparative Example 3 8 1.6 1214.5 Comparative Example 4 / / 837.1 Example 3 51 16 776.9 Example 4 42 13 814.3 Example 5 49 15 795.2 Example 6 48 15 753.8 Example 7 57 18 728.3
[0141] As shown in Table 1, the resistivity of the carbon nanotube / graphite hybrid materials synthesized in Examples 1 to 7 and Comparative Examples 1 to 3 is significantly different, but it can be seen that the higher the yield, the lower the resistivity; comparing Examples 1 to 7 with Comparative Examples 1 to 3, it can be seen that the use of polyoxyethylene ether nonionic surfactants to modify expanded graphite and the use of iron citrate as the source of the catalyst active component Fe can effectively increase the growth rate of CNT. In addition, when the proportion of CNT is the same, the powder resistivity of Example 1 (KNG-CG) is lower than that of Comparative Example 4 (KNG-C / G), indicating that the use of CVD to synthesize carbon nanotube / graphite hybrid materials can reduce the contact resistance of the two materials.
[0142] The following application examples are used to illustrate the application of the composite materials prepared in the examples and comparative examples in lithium batteries; unless otherwise specified, the parts are by mass.
[0143] Application Example 1
[0144] 25 parts of positive electrode material lithium nickel cobalt manganese oxide (LiNi 0.6 Co 0.2 Mn 0.2 O2, NCM), 7.14 parts of carbon nanotube / graphite hybrid material KNG-CG, 3.57 parts of binder PVDF and 71.4 parts of solvent N-methylpyrrolidone were added into the material tank and ball milled for 1 hour to obtain the positive electrode slurry;
[0145] The positive electrode slurry was coated on the positive electrode current collector aluminum foil (thickness was 200 μm), first dried at 80° C. for 1 hour, and then transferred to a vacuum drying oven and dried at 120° C. for 6 hours to obtain a positive electrode sheet.
[0146] Negative electrode: lithium sheet (thickness 0.5mm).
[0147] Separator: porous polypropylene film (thickness 25 μm).
[0148] The electrolyte composition is 1M lithium hexafluorophosphate (LiPF6), and the solvent composition (mass percentage) is: 30% ethylene carbonate (EC), 50% dimethyl carbonate (DMC), and 20% ethyl methyl carbonate (EMC).
[0149] The positive electrode sheet, separator and negative electrode sheet were cut and assembled in a glove box, so that the separator was placed between the positive electrode sheet and the negative electrode sheet to play an isolating role. The separator was soaked with electrolyte and compacted to obtain a button-type lithium-ion battery, which was recorded as NCM-KNG-CG.
[0150] Application Comparative Example 1
[0151] A button-type lithium-ion battery was prepared by referring to the method of Application Example 1, except that the carbon nanotube / graphite hybrid material KNG-CG was replaced by the carbon nanotube / graphite composite material KNG-C / G of Comparative Example 4. The prepared button-type lithium-ion battery was recorded as NCM-KNG-C / G.
[0152] The following electrochemical performance tests were performed on the lithium electronic batteries prepared in the above application examples and application comparison examples.
[0153] 1. Impedance test
[0154] The EIS of the battery was obtained using Shanghai Chenhua electrochemical workstation CHI600E, and the test frequency range was between 0.1 Hz and 1 MHz.
[0155] 2. Rate performance
[0156] The Xinwei constant temperature integrated battery test cabinet (MIHW-200-160CH) is used to test the battery rate performance.
[0157] At 25°C, the battery was charged and discharged in a short cycle at low current (0.1, 0.2, 0.5C), and then cyclically charged and discharged at different rates (1C, 2C, 3C, 5C, 7C), and the discharge specific capacity after each cycle was recorded.
[0158] 3. Cycle stability performance
[0159] Under a constant temperature environment of 25°C, charge to 4.2V at 1C, then charge at a constant voltage at 4.2V to a current ≤1 / 20C, let stand for 5 min, then discharge to 2.75V at 1C, record the discharge specific capacity Dn (n=1, 2, ...), repeat the previous process until the number of cycles reaches 100, record the capacity fading value of each cycle, and obtain the capacity retention rate (%) = (Dn / D1) × 100%.
[0160] The impedance test results are as follows: Figure 2As shown, the horizontal axis Z' represents the real part of the impedance, and the vertical axis Z" represents the negative number of the imaginary part. It can be seen from the figure that compared with NCM-KNG-C / G, the NCM-KNG-CG battery exhibits low resistance. This is due to the fact that KNG-CG assembled by chemical bonding reduces the contact resistance, while also improving the dispersion between carbon nanotubes and graphite, and constructing a good conductive network in the electrode material, so that the NCM-KNG-CG battery exhibits a relatively low internal resistance.
[0161] The rate performance test results are as follows: Figure 3 As shown in the figure, it can be seen that the NCM-KNG-CG battery can still maintain a high capacity at high rates, while the capacity attenuation of the NCM-KNG-C / G battery at high rates is more serious.
[0162] Cycling stability results: The first discharge specific capacity of the NCM-KNG-CG battery is 137mAh / g, the capacity retention rate after 50 cycles is 92%, and the capacity retention rate after 100 cycles is 75%; the first discharge specific capacity of the NCM-KNG-C / G battery is 125mAh / g, the capacity retention rate after 50 cycles is 88%, and the capacity retention rate after 100 cycles is 32%. It can be seen that at a current density of 1C, the cycling stability of the NCM-KNG-CG battery is significantly better than that of the NCM-KNG-C / G battery. The former can still maintain a specific capacity of 75% of the initial capacity after 100 cycles of charge and discharge, while the performance of the NCM-KNG-C / G battery drops severely after 100 cycles (the capacity retention rate is 32%).
[0163] In summary, the preparation method of the present application effectively improves the blending dispersion of carbon nanotubes and graphite, reduces the contact resistance between carbon nanotubes and graphite, and the prepared carbon nanotube / graphite hybrid material has high conductivity and achieves good results in lithium batteries.
[0164] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.
Claims
1. A method for preparing a carbon nanotube / graphite hybrid material, characterized in that: include: (1) Preparation of metal-supported graphite catalyst 1-1) mixing a surfactant, expanded graphite and water and performing a first stirring to obtain a graphite dispersion, and then removing water from the graphite dispersion to obtain modified graphite; wherein the surfactant comprises a nonionic surfactant; 1-2) mixing the modified graphite, a soluble metal salt, water and an optional ammonium salt and performing a second stirring to obtain a metal salt-graphite dispersion; wherein the soluble metal salt comprises a main catalyst salt and an optional auxiliary catalyst salt, the main catalyst salt comprises iron citrate, and the auxiliary catalyst salt comprises a molybdenum salt; 1-3) removing water from the metal salt-graphite dispersion, and calcining the obtained solid product at 300-500° C. to obtain a metal-supported graphite catalyst; (2) Preparation of carbon nanotube / graphite hybrid materials Under the protection of inert gas, the metal-supported graphite catalyst is brought into contact with a reducing gas and a carbon source gas, and the carbon source gas is used to perform chemical vapor deposition to form carbon nanotubes, thereby obtaining a carbon nanotube / graphite hybrid material.
2. The preparation method according to claim 1, characterized in that: In step 1-1), the nonionic surfactant is a polyoxyethylene ether surfactant; Preferably, the polyoxyethylene ether surfactant is selected from alkylphenol polyoxyethylene ether and / or fatty alcohol polyoxyethylene ether; Preferably, the polyoxyethylene ether surfactant is selected from one or more of octylphenol polyoxyethylene ether, nonylphenol polyoxyethylene ether, dodecylphenol polyoxyethylene ether, dinonylphenol polyoxyethylene ether and lauryl alcohol polyoxyethylene ether; Preferably, the mass ratio of the surfactant to the expanded graphite is (2-10):100; Preferably, the mass ratio of the expanded graphite to water is (15-30):100; Preferably, the first stirring temperature is 20-40°C, and the stirring time is 0.5-2h; Preferably, the method of removing water from the graphite dispersion comprises: stirring the graphite dispersion at 50-80° C. for 2-8 hours.
3. The preparation method according to claim 1 or 2, characterized in that: The iron citrate is ammonium ferric citrate and / or ferric citrate, more preferably ammonium ferric citrate; Preferably, the ammonium salt is at least one of ammonium carbonate and ammonium bicarbonate; Preferably, the iron citrate is ferric citrate, and In step 1-2), the mass ratio of ferric citrate to ammonium salt is (2-8):
1.
4. The preparation method according to any one of claims 1 to 3, characterized in that In step 1-2), the mass ratio of the main catalyst salt to the auxiliary catalyst salt is (15-30):1, and the mass ratio of the soluble metal salt to the modified graphite is (1.2-3):1; Preferably, the mass ratio of the soluble metal salt to water is (30-50):100; Preferably, the main catalyst salt also includes a cobalt salt; Preferably, the cobalt salt is cobalt nitrate and / or cobalt nitrate hydrate; Preferably, the mass ratio of the iron citrate to the cobalt salt is (3-10):
1.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The molybdenum salt is ammonium molybdate and / or ammonium molybdate hydrate.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The second stirring temperature is 50-80°C and the stirring time is 1-5h; Preferably, the method of removing water from the metal salt-graphite dispersion comprises: stirring the metal salt-graphite dispersion at 100-180° C. for 2-6 hours.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The calcination is carried out in an oxygen-containing atmosphere, and the calcination time is 1 to 5 hours.
8. The preparation method according to any one of claims 1 to 7, characterized in that: In the chemical vapor deposition, relative to 3 g of the metal-supported graphite catalyst, the flow rate of the reducing gas is 80 to 120 sccm, and the flow rate of the carbon source gas is 800 to 1500 sccm; Preferably, the carbon source gas is selected from at least one of methane, acetylene, ethylene and propylene; Preferably, the reducing gas is hydrogen; Preferably, the chemical vapor deposition temperature is 600-800° C. and the time is 30-60 min.
9. A carbon nanotube / graphite hybrid material prepared by the preparation method according to any one of claims 1 to 8.
10. A lithium ion battery, characterized in that: Contains a conductive additive, wherein the conductive additive comprises the carbon nanotube / graphite hybrid material according to claim 9.
Citation Information
Patent Citations
Conductive additive for preparing power lithium ion battery cathode material and preparation method thereof
CN102610827A
Cited By
Carbon nanotube / graphite hybrid material and preparation method therefor, and lithium-ion battery
WO2026143899A1